Joining of galvannealed steel and aluminium alloy using controlled short circuiting gas metal arc welding process. (26th May 2015) - Das, A.; Shome, M.; Das, C. R.; Goecke, Sven-F; De, A.
Abstract : Controlling the Fe–Al intermetallic layer thickness along the joint interface has remained a critical challenge in gas metal arc welding of galvanised steel and aluminium alloys. An attempt is presented here to join galvannealed steel and aluminium alloy sheets using a novel gas metal arc welding process that allows controlled short circuiting to reduce the rate of heat input significantly. The real time current and voltage transients during the process are monitored to estimate the rate of heat input and its influence on the formation of intermetallic phases and layer thickness. The results show that the intermetallic layer thickness can be controlled and good joint strengths can be achieved when the rate of heat input remains lesser than 130 J mm − 1 for the typical lap joint configuration considered here.